Non-disruptive error field measurement in DIII-D low safety factor plasmas and projection to ITER - Q.M. Hu; N.C. Logan; C. Paz-Soldan; J. Barr; S.K. Kim; J. Hanson; Y.Z. Jiang; S.M. Yang; A. Bortolon; W. Choi; Y.Q. Liu; J.-K. Park; et al. (Nuclear Fusion)
Previous experiments in DIII-D (Paz-Soldan et al 2022 Nucl. Fusion 62 126007) introduced a method to identify intrinsic error fields (EFs) in tokamaks with minimal disruption risk by promptly healing driven magnetic islands during the conventional ‘compass scan’. This paper presents recent experimental and numerical advancements in extending this approach to low q _95 plasmas, and projects its applicability to ITER. Non-disruptive EF measurement is achieved at q _95 = 4.5 and 3.9 without any initial EF correction (EFC) by reducing the time between the occurrence of the locked mode (LM) and control action to 10 ms and increasing the density 50%–100%. However, 50% correction of the intrinsic EF is required to achieve island healing at q _95 = 3.2 with 10 ms delay for the control action. Nonlinear two-fluid modeling with the TM1 code reproduces the DIII-D experimental observations, indicating that promptly turning off the 3D coil current reduces both magnetic island width and electromagnetic force, while raising the density increases plasma viscosity, facilitating magnetic island healing. The simulations show that for scenarios with q _95 = 3.2, lowering the control action time to 5 ms will lead to island healing without EFC. TM1 simulations are extended to future ITER scenarios with 5 MA and 7.5 MA plasma currents, predicting the dependence of required density rise on action time and EF amplitude. These simulations indicate that, benefiting from the much longer resistive time, island healing can be successfully achieved in ITER when taking control action 100–500 ms after a LM occurrence.